Understanding the associations across fibromyalgia-related fatigue, depression, anxiety, self-esteem satisfaction with life and physical activity in portuguese and brazilian patients: a structural equation modeling analysis - Alvarez, Marcos C. (2022)
Background and Objectives: Fibromyalgia are heterogeneous and differ from patient to patient; however, the most reported are general myalgia and at specific points associated with fatigue and certain psychological adversities. Physical activity can mitigate the effects of the symptoms. However, the associations between fibromyalgia-related fatigue, self-esteem, anxiety, depression, satisfaction with life and physical activity are unclear. Therefore, the aim of the present study was to understand the associations between these symptoms and whether there are differences between these associations across two distinct cultures. Materials and Methods: A total of 473 women aged between 28 and 75 years (M = 49.27; SD ± 8.28) completed five questionnaires about fibromyalgia-related fatigue, physical activity, anxiety, depression, self-esteem, and satisfaction with life. Results: Fibromyalgia-related fatigue was positively associated with depression and anxiety, depression and anxiety were negatively associated with self-esteem, self-esteem was positively associated with satisfaction with life, satisfaction with life was positively associated with physical activity and there were no differences in terms of the perceptions and associations of these variables between Portuguese and Brazilian patients. Conclusions: Our results showed the significant role of associations between these variables and a similarity in the perception and relationship of the variables between the two cultures.